Nutritional interventions in prevention of chronic diseases - phytochemicals as sirtuin activators and their role in the regulation of metabolic processes - Klaudia Michalak; Kacper Janowski; Tomasz Poboży; Emilia Piotrowicz; Paweł Jan Kuna; Alicja Katarzyna Chojniak; Dagmara Neska (Quality in Sport, 2025)
Introduction: Diet plays a crucial role in preserving health and enhancing overall wellness. Dietary phytochemicals are naturally occurring substances found in foods that may be beneficial in preventing chronic conditions. Sirtuins (SIRTs) are part of a group known as class III NAD-dependent histone deacetylases, which are important in key cellular functions. They participate in multiple processes, such as the balance between oxidants and antioxidants, controlling inflammation, insulin sensitivity, fatty acid metabolism, and aging. The involvement of sirtuin activation through the action of phytochemicals contained in natural products has been described as potentially beneficial in many chronic diseases such as obesity, type 2 diabetes and cardiovascular diseases. In this review, we discussed how selected phytochemicals influence the activation of sirtuins and the impact of their intake on the development and progression of chronic illnesses.